PRIMARY DYSMENORRHEA AMONG STUDENTS AT LIRA UNIVERSITY IN NORTHERN UGANDA: SYMPTOMS PRESENTATION AND MANAGEMENT - A QUANTITATIVE STUDY. - Ikwara, Emmanuel Asher; Atwijukiire , Humphrey (Student’s Journal of Health Research Africa, 2024)
Background: Primary dysmenorrhea (PD) is menstrual pain not associated with any pelvic pathology. It is one of the most common gynecologic complaints in young women. In Uganda, literature is scarce on the PD-associated symptoms and management strategies used by women of reproductive age. This study aimed to describe primary dysmenorrhea-associated symptoms and management strategies used by undergraduate students in northern Uganda. Methods: A non-experimental cross-sectional study design was used using descriptive methods of data analysis. The study was conducted among female undergraduate students of a University in Lira, northern Uganda. Systematic sampling was used to select study participants who met the inclusion criteria until 232 study participants were recruited. The data was collected using a self-administered questionnaire. Data analysis was aided by Statistical Package for Social Sciences (SPSS) (version 23) and descriptive statistics were used. Results: The prevalence of PD was 90.9%. The most commonly experienced dysmenorrhea-associated symptoms were change in appetite (36.0%), breast engorgement (39.8%), and depressed mood (51.4%). Pain relievers were the most commonly used management strategy (77%) with Paracetamol being the most commonly used pain reliever (29.8%). The most commonly used non-pharmacological management strategies were; exercise (47.6%), resting (44.5 %), and relaxation (44.1%). Conclusion: The prevalence of PD was high among the study participants. The most common symptoms experienced by those with PD were; depressed mood, breast engorgement, and change in appetite. The most commonly used management strategies for PD were pain relievers, exercise, rest, and relaxation. University management should prioritize menstrual health and design programs to educate female students on the management of dysmenorrhea-associated symptoms using both pharmacological and non-pharmacological strategies. Recommendation: We recommend the university prioritize education, conduct awareness campaigns, ensure access to resources and counseling, collaborate with healthcare, develop policies, and continue research.